KONFLIK KEPENTINGAN ANTARA AMERIKA DAN KELOMPOK ISLAM FUNDAMENTALIS - Chairil N. Siregar (Jurnal Sosioteknologi, 2009)
The United States is a super power country. Its potential human resources and advanced economy are the powerful weapons for the US to dominate the wolrd economy. Several ways are done to ful fil the anbition. To achieve if, the US after breaks orther countries' right, especully if the majority of those countries' people are moslem. This appenrs the action to oppose the US. The struggle of fundamentalist moslem activits againts those who take sides with the Us After happened. This article disausses the conflict of interest between the Us and the fundamentalist moslem activist groups.